Description of a new genus and two new species of high frequency cicada from New Caledonia (Insecta: Hemiptera, Cicadoidea, Cicadidae) - Delorme, Quentin; Mille, Christian; Jourdan, Hervé (Zootaxa, 2016)
The new genus Murmurillana Delorme gen. nov., is described within the tribe Cicadettini Buckton, 1889, designating Murmurillana inaudibilis Delorme sp. nov., as the type species. Murmurillana inaudibilis Delorme sp. nov. and Murmurillana paenetacita Delorme sp. nov. are described from New Caledonia. They are respectively found in mid altitude dense Niaouli shrub (Melaleuca quinquenervia, Myrtaceae) vegetation, mixed with dense fern cover (Pteridium sp., Dennstaedtiaceae) on the Massif of Aoupinié (800 m) and on foothills of the Mont Panié (570 m). Male calling songs of the two new species are described from field recordings. These calling songs exhibit unusually high dominant frequencies. A key to the species of Murmurillana Delorme gen. nov., is also provided.